Stability evaluation of organic Lip Balm (Brazilian Journal of Pharmaceutical Sciences, 2013)
Rising global demand for natural products whose production is harmless to the environment has stimulated the development of natural cosmetics and, within this category, organics (95% organic raw materials). The image of environmentally friendly production is one of the strongest attractions of organic products. Lip balm is a cosmetic product similar to lipstick whose purpose is to prevent lip dryness and protect against adverse environmental factors. The product's characteristics are: resistance to temperature variations, pleasant flavor, innocuousness, smoothness during application, adherence and easy intentional removal. This work involved the development of a lip balm formulated with certified organic raw materials and the execution of stability tests: fusion point determination, evaluation of organoleptic characteristics (color, odor and appearance) and functionality evaluation (spreadability test). The formulation selected after the Preliminary Stability Test was submitted to the Normal Stability Test under the following storage conditions (temperature): Room Temperature (22.0 ± 3.0 ºC), Oven (40.0 ± 2.0 ºC) and Refrigerator (5.0 ± 1.0 ºC), for 90 days. Under the Refrigerator and Room Temperature conditions, spreadability proved adequate, but the surface presented white spots, characterizing the fat bloom, a phenomenon involving the recrystallization of cocoa butter. Storage at 40.0 ± 2.0 ºC (Oven) caused loss of functionality according to the spreadability test, in addition to changes in color, although the aspect was uniform since the fat bloom was not observed (white spots on the surface). The odor remained stable under all conditions as did the melting point, which had a mean of 72.9 ± 1.7 ºC throughout the course of stability testing (90 days).